Children poisoning by carbamate: a descriptive study - Vieira, Luiza Jane Eyre de Souza (2012)
The study had as its aim to characterize the children under 5 years old, attended with exogenous poisoning by carbamate (popularly called “chumbinho” – “small shot”) at an emergency hospital in Fortaleza and to relate the signs and symptoms detected in this type of poisoning. It concerned a descriptive study, with a sample of 65 children attended during the period of 1998 to 2000, in Fortaleza, Ceará. It was noticed that the most affected age group was of those with 1 to 3 years old, not being verified any significant difference between sexes. The most evident signs and symptoms were myosis, vomits, profuse perspiration and sialorrhea and the predominant treatment was the use of active coal. It is concluded, therefore, that there is a need of putting into effect the health education, calling the society’s attention to the risks of the inadequate “chumbinho” use in the domiciliar environment.